2000
DOI: 10.1111/j.1939-1676.2000.tb02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of a Rice‐Based Oral Rehydration Solution Given to Normal Calves

Abstract: The objective of the study was to test the tolerance of a rice-based oral rehydration formula when fed to calves. Six healthy Holstein calves, 1 week of age, were fed the formula instead of milk replacer for 3 days. Pre-and posttreatment results of clinical examination and laboratory parameters were compared. Vital signs, attitude, appetite, clinical hydration status, urine specific gravity, and most routine serum biochemistry test results did not vary and remained within the normal range. Five of the 6 calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Supporting our results, a previous study reported that the use of an oral electrolyte containing rice, promoted diarrhea in young calves less than 2 weeks old [21]. Pre-ruminant calves lack the production of enzymes to digest maltose and starch from rice and this situation might lead to osmotic diarrhea when it is provided in milk replacers or in oral electrolytes [21, 22]. This fact might explain the increase in the days SRB calves spent in the moderate and severely sick categories in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Supporting our results, a previous study reported that the use of an oral electrolyte containing rice, promoted diarrhea in young calves less than 2 weeks old [21]. Pre-ruminant calves lack the production of enzymes to digest maltose and starch from rice and this situation might lead to osmotic diarrhea when it is provided in milk replacers or in oral electrolytes [21, 22]. This fact might explain the increase in the days SRB calves spent in the moderate and severely sick categories in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to our expectations, SRB calves that were healthy at enrollment presented a moderate health status earlier than healthy CTR calves. Even though these differences were not significant, we attribute this finding to a possible osmotic effect of SRB on the large intestine of young animals [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation